Bandgap Engineering of Organic Semiconductors for Highly Efficient Photocatalytic Water Splitting. Issue 24 (28th June 2018) - Wang, Yiou; Silveri, Fabrizio; Bayazit, Mustafa K.; Ruan, Qiushi; Li, Yaomin; Xie, Jijia; Catlow, C. Richard A.; Tang, Junwang
Abstract: The bandgap engineering of semiconductors, in particular low‐cost organic/polymeric photocatalysts could directly influence their behavior in visible photon harvesting. However, an effective and rational pathway to stepwise change of the bandgap of an organic/polymeric photocatalyst is still very challenging. An efficient strategy is demonstrated to tailor the bandgap from 2.7 eV to 1.9 eV of organic photocatalysts by carefully manipulating the linker/terminal atoms in the chains via innovatively designed polymerization. These polymers work in a stable and efficient manner for both H2 and O2 evolution at ambient conditions (420 nm < λ < 710 nm), exhibiting up to 18 times higher hydrogen evolution rate (HER) than a reference photocatalyst g‐C3 N4 and leading to high apparent quantum yields (AQYs) of 8.6%/2.5% at 420/500 nm, respectively. For the oxygen evolution rate (OER), the optimal polymer shows 19 times higher activity compared to g‐C3 N4 with excellent AQYs of 4.3%/1.0% at 420/500 nm. Both theoretical modeling and spectroscopic results indicate that such remarkable enhancement is due to the increased light harvesting and improved charge separation. This strategy thus paves a novel avenue to fabricate highly efficient organic/polymeric photocatalysts with precisely tunable operation windows and enhanced charge separation. Abstract : A polymerization‐controlled strategy is demonstrated to synthesize a group of organic semiconductors with stepwise tunable bandgaps for highly efficient H2 and O2 evolution from water under visible light with 18 and 19 times higher activities than g‐C3 N4 . Experimental and theoretical results reveal that the surprising performance is mainly due to the narrowed bandgap and enhanced charge separation.